Hapū Ora (pregnancy wellness): Māori research responses from conception, through pregnancy and 'the first 1000 days' – a call to action for us all. Issue 4 (8th August 2022) - Edmonds, Liza K.; Cram, Fiona; Bennett, Matthew; Lambert, Charlie; Adcock, Anna; Stevenson, Kendall; Geller, Stacie; MacDonald, Evelyn Jane; Bennett, Tina; Storey, Francesca; Gibson-Helm, Melanie; Ropitini, Sidney; et al.
ABSTRACT: Aims: To describe a body of Māori translational research responses that challenge colonialised systems. Methods: To delineate and link ongoing Kaupapa Māori and Māori-led translational research. Results: He Tapu Te Whare Tangata explores human papilloma virus (HPV) screening. Te Hā o Whānau presents a culturally responsive framework of maternity care. E Hine describes young Māori mothers' experiences of Hapū Ora. Severe Acute Maternal Morbidity (SAMM) and SAMM Kids identify opportunities to improve avoidable morbidity. He Tamariki Kokoti Tau – Babies born prematurely, is a qualitative study of Māori experiences of preterm birth. He Tamariki Kokoti Tau – Tackling Preterm, is a quantitative analysis. He Korowai Manaaki is a wraparound maternity pathway. Whānau Manaaki – Methamphetamine aims to reduce the impact of methamphetamine. Calls for action reflect shared desires for system transformation. Conclusion: We lay the wero (challenge) down to all to transform our current systems. Action is needed! Abbreviations : HPV: human papilloma virus, SAMM: severe acute maternal morbidity, ICU: intensive care unit, HDU: high dependency unit, RCT: randomised controlled trial, HQSC: Health Quality and Safety Commission.